Exploring Stress Levels of Anganwadi Workers during the COVID-19 Pandemic - Preeti; Vandana; Rani, Ella (International Journal of Bio-resource and Stress Management, 2025)
The study was conducted during January to July, 2022 under the Department of Extension Education and Communication Management, College of Community Science, CCSHAU, Hisar, Haryana, India to identify stress level of Anganwadi workers in performing their activities during COVID-19 pandemic and the probable reasons for stress. Two blocks in the state of Haryana's Hisar district were used for the study. Ten villages were covered in order to randomly chosen 100 Anganwadi workers. The villages were chosen by random sampling, and Anganwadi staff were reached by chain technique. Survey was used to measure stress levels, and in-depth interview was conducted in a variety of rural locations to obtain qualitative insights. The stress level of Anganwadi workers was assessed by using Cohen’s Perceived stress scale and the “Ardell Wellness Stress Test” used for self-assessment by incorporated physical, mental, emotional, spiritual and social aspect of health. The study concluded that 58.00 per cent of Anganwadi workers felt moderate stress during COVID-19 pandemic. They were unable to handle personal problem like child care, household work, family related matters during COVID-19. Many unexpected things happened in their surroundings. They felt stress because they could not overcome the problems and unable to control the things of life. Probable reasons for stress were that more than half of respondents (55.73%) had less knowledge regarding personal hygiene practices and food hygiene.